Selective Functionalization of Aliphatic Amines via Myoglobin-Catalyzed Carbene N–H Insertion - Steck, Viktoria; Sreenilayam, Gopeekrishnan; Fasan, Rudi (Synlett, 2020)
Engineered myoglobins have recently gained attention for their ability to catalyze a variety of abiological carbene transfer reactions including the functionalization of amines via carbene insertion into N–H bonds. However, the scope of myoglobin and other hemoprotein-based biocatalysts in the context of this transformation has been largely limited to aniline derivatives as the amine substrates and ethyl diazoacetate as the carbene donor reagent. In this report, we describe the development of an engineered myoglobin-based catalyst that is useful for promoting carbene N–H insertion reactions across a broad range of substituted benzylamines and α-diazo acetates with high efficiency (82–99% conversion), elevated catalytic turnovers (up to 7,000), and excellent chemoselectivity for the desired single insertion product (up to 99%). The scope of this transformation could be extended to cyclic aliphatic amines. These studies expand the biocatalytic toolbox available for the selective formation of C–N bonds, which are ubiquitous in many natural and synthetic bioactive compounds.
Keywords: biocatalysis; myoglobin; protein engineering; C–N bond formation; carbene N–H insertion